2012
DOI: 10.4236/ajac.2012.310090
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heavy Metals at Sub-ppb Levels in Water by Graphite Furnace Atomic Absorption Spectrometry Using a Direct Introduction Technique after Preconcentration with an Iminodiacetate Extraction Disk

Abstract: A direct analysis method combining an iminodiacetate extraction disk (IED) with graphite furnace atomic absorption spectrometry was developed for the determination of Co, Ni, Cu, Cd, Sn, Pb, and Bi at sub-ppb levels in water. A 100 mL water sample was adjusted to pH 5.6 with nitric acid and a 1 mol·L -1 ammonium acetate solution, and then passed through an IED (diameter, 47 mm; effective filtering diameter, 35 mm) at a flow rate of 80 -100 mL·min -1 to preconcentrate seven analytes. The IED was dried at 100˚C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Examination of heavy metals in drinking water samples of different universities showed that the number of metals was higher than the allowable limit (10 mg/l) in some samples [22]. The amount of toxic metal arsenic in the university with the codes 1-1, 1-2, and 6 is higher than the allowable level, and it is necessary to take the necessary measures to follow up the pollution and eliminate it.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of heavy metals in drinking water samples of different universities showed that the number of metals was higher than the allowable limit (10 mg/l) in some samples [22]. The amount of toxic metal arsenic in the university with the codes 1-1, 1-2, and 6 is higher than the allowable level, and it is necessary to take the necessary measures to follow up the pollution and eliminate it.…”
Section: Discussionmentioning
confidence: 99%
“…Atomic absorption spectroscopy (AAS), inductively coupled plasma optical emission spectroscopy (ICP-OES), and mass spectroscopy (ICP-MS) are among the most common analytical techniques for the determination of heavy metals. 7,8 They show excellent sensitivity, and some are with multi-element analysis capability ( i.e. ICP-OES and ICP-MS).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to determine the heavy metal content of environmental samples [3] the most popular methods for this purpose at present are atomic absorption spectrometry (AAS), inductively coupled plasma-atomic emission spectrometry (ICP-AES) and instrumental neutron activation analysis (NAA). The necessity of a nuclear reactor for NAA, the necessity of exhaustively prepare the samples (depending on the matrix) for AAS and ICP-AES, however, stimulate the interest towards energy dispersive X-ray spectrometry (EDXRF) in ecological investigations [3]. EDXRF is a non-destructive and multi-elemental technique which can be applied to any kind of sample, liquid, solid, thick, intermediate or thin, with, in many cases, sufficient sensitivity for many trace elements [4] and EDXRF technique combined with simple procedures of sample preparation such as drying of a few droplets of liquid on filter paper allow measurement of calcium, potassium, chlorine, sulfur and phosphorus in blood serum and in cellular fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the trace elements known to be essential are As, Co, Cu, Fe, Mn, Ni, Zn, Pb and Cd [2]. Therefore, it is important to determine the heavy metal content of environmental samples [3] the most popular methods for this purpose at present are atomic absorption spectrometry (AAS), inductively coupled plasma-atomic emission spectrometry (ICP-AES) and instrumental neutron activation analysis (NAA). The necessity of a nuclear reactor for NAA, the necessity of exhaustively prepare the samples (depending on the matrix) for AAS and ICP-AES, however, stimulate the interest towards energy dispersive X-ray spectrometry (EDXRF) in ecological investigations [3].…”
Section: Introductionmentioning
confidence: 99%